KEHARUSAN PENDAMPINGAN PENASEHAT HUKUM DALAM PENANGANAN ANAK YANG BERHADAPAN DENGAN HUKUM - Paramita Martha, I Dewa Agung Ayu; Pujawan, I Made (Kertha Wicara : Journal Ilmu Hukum; Vol. 02, No. 02, April 2013)
Children are part of the younger generation, the successor to the ideals of the nationthat requires guidance and protection in order to ensure the growth and development of thephysical, mental and social development as a whole, harmonious and balanced, which doesnot have the ability to distinguish the action is allowed and not allowed, so often due to theiractions must be confronted with the law. Against children in conflict with the law that theycan not protect his own rights, there needs to be control from adults, in this case the parentand related judicial proceedings in the course of a legal aid lawyer. Therefore, in this paperwill discuss what legislation governing child protection rights of children in conflict with thelaw and whether the child is dealing with the current legal counsel has obtained assistancewhen dealing with the law.
Keywords: Children Against The Law, Children' s Rights, Legislation, Legal Aid (Legal Counsel).